Waqf For Higher Education: A Bibliometric and Systematic Literature Review (2012–2024) - Sitorus, Iwan Romadhan; Aly, Hery Noer; Lubis, Mawardi (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose:This article examines the development of waqf for higher education studies from five perspectives: (1) research development and distribution; (2) research topics; (3) main contributors; (4) recent collaboration patterns; and (5) most influential documents in waqf for higher education literature.Design/Methodology:This study involved a comprehensive bibliometric analysis and a systematic literature review, which were utilized to examine 162 documents related to waqf for higher education that were published between 2012 and 2024. The data processing was facilitated by Publish or Perish, Microsoft Excel, and VOSviewer software.Findings:Despite the long-standing existence of waqf literature, the focus on waqf for higher education was not identified until 2012 (RQ1). We identified eight distinct clusters of research topics: community welfare, waqf models for higher education, waqf in Malaysia, good management, practice, alternative sources, cash management, and waqf knowledge (RQ2). A subsequent analysis of the authorship and affiliation patterns revealed a preponderance of researchers based in Malaysia across all categories (RQ3, RQ4, RQ5).Practical Implications:Future research topics on waqf for higher education should be limited to conceptual studies or literature reviews, with a focus on best practices in universities, collaborative financing or subsidies, waqf sustainability, and waqf in the Western world.Originality/Value:This article boasts a more extensive database than previous studies, thus ensuring a more robust foundation for future research. Moreover, given the paucity of literature on the subject, it is imperative to continue documenting the evolution of waqf for higher education literature.